2009
DOI: 10.1007/s12011-009-8382-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum Fluoride and Sialic Acid Levels in Osteosarcoma

Abstract: Osteosarcoma is a rare malignant bone tumor most commonly occurring in children and young adults presenting with painful swelling. Various etiological factors for osteosarcoma are ionizing radiation, family history of bone disorders and cancer, chemicals (fluoride, beryllium, and vinyl chloride), and viruses. Status of fluoride levels in serum of osteosarcoma is still not clear. Recent reports have indicated that there is a link between fluoride exposure and osteosarcoma. Glycoproteins and glycosaminoglycans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…A study did find a link between mean fluoride levels in blood serum and increased osteosarcoma risk, but finding this association does not infer causality 52 . Mean fluoride levels in cases with other bone-forming tumours were significantly higher when compared with the control group consisting of patients with musculo-skeletal pain only.…”
Section: Discussionmentioning
confidence: 95%
“…A study did find a link between mean fluoride levels in blood serum and increased osteosarcoma risk, but finding this association does not infer causality 52 . Mean fluoride levels in cases with other bone-forming tumours were significantly higher when compared with the control group consisting of patients with musculo-skeletal pain only.…”
Section: Discussionmentioning
confidence: 95%
“…They found that, compared to control groups, serum sialic acid concentration was significantly increased in patients with osteosarcoma and, in a second study, in patients with other bone tumors (Sandhu et al, 2011). …”
Section: Osteosarcomamentioning
confidence: 93%
“…Based on the concept that glycoproteins and glycosaminoglycans are an integral part of bone and prolonged exposure to fluoride for long duration has been shown to cause degradation of collagen and ground substance in bones, Sandhu et al (2011) analyzed serum fluoride, sialic acid, calcium, phosphorus, and ALP levels in patients with osteosarcoma. They found that, compared to control groups, serum sialic acid concentration was significantly increased in patients with osteosarcoma and, in a second study, in patients with other bone tumors (Sandhu et al, 2011).…”
Section: Osteosarcomamentioning
confidence: 99%
“…This indicated that the human osteosarcoma cells expressed both forms of Sia-containing glycoconjugates and the differences in the amounts of each of the two major Sia types and their distribution may be related to the morphology and/or metastatic of osteosarcoma 15 . Another studies of Sia level in the serum reported that the amount of Sia in the serum of osteosarcoma patients was higher than in the control group, but did not differ from those of other bone-forming groups 16 . However, the accumulated data on the level and distribution of Sia in osteosarcoma is still limited.…”
Section: Discussionmentioning
confidence: 90%
“…A significant elevation of the total Sia level was found when compared with that level in the control sera. However, an increase of the Sia level was also found in the sera of patients with other boneforming tumours 16 . Here, to better understand the relation of elevated Sia and the pathology of osteosarcoma, osteosarcoma cells were isolated from bone samples of 7 patients with osteosarcoma.…”
Section: Introductionmentioning
confidence: 88%